Understanding and experiencing life satisfaction from the mothers perspective - Gregorczuk-Prosicka, Joanna (Difficult situation in biographies: Volume 9, 2025)
Life satisfaction is understood as a subjective assessment of one’s own existence in relation to the standards one has adopted. The article presents the results of research aimed at analyzing mothers’ understanding of the concept of life satisfaction and showing the relationship between motherhood and the sense of life satisfaction. The term life satisfaction is a complex term and its complexity is presented graphically in the text. After the analysis and interpretation, implications for further research and practice guidelines related to the increasingly discussed topic of parental burnout are indicated.